Magnetic Resonance Imaging of the Temporal Lobe: Normal Anatomy and Diseases. Issue 2 (May 2014) - Khashper, Alla; Chankowsky, Jeffrey; del Carpio-O'Donovan, Raquel
Objective: This pictorial essay will review the magnetic resonance imaging anatomy of the temporal lobes and describe the major pathologic processes of this complex area. Conclusions: Magnetic resonance imaging is an essential tool in the investigation of a patient with suspected temporal lobe pathology. Various conditions may affect this anatomic region, and, therefore, classification of imaging findings into specific groups may help provide a more focused differential diagnosis.